The Cambridge companion to the city in literature - McNamara, Kevin R, Ed (Cambridge companions to literature, 2014)
"From the myths and legends that fashioned the identities of ancient city-states to the diversity of literary performance in contemporary cities around the world, literature and the city are inseparably entwined. The international team of scholars in this volume offers a comprehensive, accessible survey of the literary city, exploring the myriad cities that authors create and the genres in which allegorical cities appear. Early chapters consider the literary legacies of historical and symbolic cities from antiquity to the early modern period, while subsequent chapters consider the importance of literature to the relationship between urban landscape and memory. These later chapters explore the form of the literary city and its response to social and technological change; dystopian, nocturnal, pastoral, and sublime cities; and the cities of economic, sexual, cultural, and linguistic outsiders"--